The Sarcophagi of Saints Vitale and Agricola: «Restless» Relics and «Moving» Churches in Bologna in the 11th and 12th Centuries (Fenestella. Inside Medieval Art, 2024)
The aim of the contribution is to re-read the events in Bologna of the 11th and 12th centuries concerning the cathedral of San Pietro and the monastery of Santo Stefano / Sancta Jerusalem, starting from the discovery of the relics found in 1141. Attention was paid to their movement from one building to another within the monastery and to the fluctuating dedication of the churches, but also to the relocation of the relics in the Cathedral of San Pietro. The sarcophagi preserved in the church of Saints Vitale and Agricola are then re-examined, tracing their production, reuses and movements over the years.The most important aspect on which attention was focused, however, was the clash between the secular clergy and the monks of Santo Stefano, a clash involving the Municipality, the Empire, the Papacy, the relics of Saints Vitale and Agricola and those of San Petronio.
Keywords: Bologna; Relics; Romanesque; Holy Sepulcre